2015
DOI: 10.5325/jeasmedarcherstu.3.1.0027
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Greek Deathscapes

Abstract: Personal, yet utterly universal. Inevitable, yet unknowable. Death has been a dominant theme in all cultures since time immemorial. Central to the theme of death is the burial of the dead in cemeteries. But death also unfolds in other areas such as natural spaces, places of worship, and battlefields. These then become places of intense private and personal significance, which simultaneously act as shared collective sites of experience and remembrance. This article seeks to provide an insight into “deathscapes”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In recent years, deathscapes have been considered in relationship to theories of space-making and ontological proxies for humans. Dimakis (2015: 27) has defined deathscapes as discursive spaces: “mental constructs comprised of ideas about, and representations of, death in the landscape”; but they are also produced through diverse social and material practices that are historically constituted. Deathscapes are spaces of deep significance both personal and collective, imbued with experiences, memories, and emotions that are constructed while death is staged.…”
Section: Deathscapes and Mythologized Landscapesmentioning
confidence: 99%
“…In recent years, deathscapes have been considered in relationship to theories of space-making and ontological proxies for humans. Dimakis (2015: 27) has defined deathscapes as discursive spaces: “mental constructs comprised of ideas about, and representations of, death in the landscape”; but they are also produced through diverse social and material practices that are historically constituted. Deathscapes are spaces of deep significance both personal and collective, imbued with experiences, memories, and emotions that are constructed while death is staged.…”
Section: Deathscapes and Mythologized Landscapesmentioning
confidence: 99%
“…Thus, serious concerns have been raised regarding the future demographics of the Marau Central Cemetery. Consequently, even ignoring the settlement of migrants that come in response to a recent increasing businesses trend and who establish themselves in the area, the coming increase of the death rate looms problematic for any future government (Trindade & Neckel, 2014;Quinn, 2015;Dimakis, 2015;Klaver, 2015).…”
Section: Central Cemeterymentioning
confidence: 99%
“…In parallel with population growth, contamination generated by cemeteries has continued to increase (Quinn, 2015;Dimakis, 2015;Klaver, 2015). In general, given the size of the area they occupy, urban cemeteries are located in regions of reduced socioeconomic development, and areas economically undervalued.…”
Section: Introductionmentioning
confidence: 99%
“…John Barrett (1994) introduced the 'archaeology of inhabitation', which is almost identical to the 'dwelling perspective' that the book proposes. Burial sites have been examined as Foucauldian heterotopias in prehistoric Crete (Vavouranakis, 2007), Classical Greece (Dimakis, 2015), and Roman Asia Minor (Cormack, 2004). Barrett (2013) has also suggested that the early development of human cognition hinged upon non-discursive social interaction.…”
mentioning
confidence: 99%